The Role Of Speech Therapy In The Assessment And Rehabilitation Of Speech Function In Individuals With Cerebral Stroke - Shaboyan, Mery; Harutyunyan, Marianna; Karapetyan, Siranush; Petrosyan, Khachik; Martirosyan, Lusine; Astghik, Grigoryan (Journal of Neonatal Surgery, 2025)
Cerebral stroke often results in significant impairments in speech and language functions, severely impacting the quality of life of affected individuals. Speech therapy plays a crucial role in both the assessment and rehabilitation of speech activity in patients who have experienced a brain stroke. This paper examines the effectiveness of speech therapy interventions in restoring communicative abilities and cognitive functions affected by cerebrovascular incidents. By analyzing the latest scientific approaches and therapeutic techniques, this study highlights the importance of individualized treatment plans that address phonetic, lexical, syntactic, and prosodic disturbances. Furthermore, it discusses the integration of modern diagnostic tools and neurorehabilitation methods to optimize speech recovery outcomes. The findings demonstrate that consistent and targeted speech therapy can significantly enhance verbal communication and cognitive rehabilitation in post-stroke patients.